The Principal’s Role in Implementing a Child-Friendly School: : A Case Study at SDN 05 Bojongbata, Pemalang - Wijayanti, Dian; Kusumaningsih, Widya; Soedjono (Belajea: Jurnal Pendidikan Islam, 2024)
This study explores the role of the principal in implementing Child-Friendly Schools (Sekolah Ramah Anak) at SDN 05 Bojongbata, Pemalang. Despite increasing attention to Child-Friendly Schools in Indonesia, limited research has examined how principals apply managerial functions in this context. Using a qualitative descriptive approach with a phenomenological method, the study investigated the principals’ practices in planning, organising, mobilising, and supervising. Findings show that the principal exercised strategic and collaborative leadership by engaging teachers, parents, and students, supported by effective communication, motivation, and routine evaluations. This study contributes by linking phenomenological insights with leadership theory, showing how abstract concepts are translated into practical strategies. It emphasises that visionary, participatory leadership is essential for sustaining inclusive and safe learning environments.